2004
DOI: 10.1038/sj.cdd.4401385
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide produced by Aplysia ink toxin kills tumor cells independent of apoptosis via peroxiredoxin I sensitive pathways

Abstract: Marine snails of the genus Aplysia possess numerous bioactive substances. We have purified a 60 kDa protein, APIT (Aplysia punctata ink toxin), from the defensive ink of A. punctata that triggers cell death with profound tumor specificity. Tumor cell death induced by APIT is independent of apoptosis but is characterized by the rapid loss of metabolic activity, membrane permeabilization, and shrinkage of nuclei. Proteome analysis of APIT-treated tumor cells indicated a modification of peroxiredoxin I, a cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…PRDX1 expression is also elevated in most cancers, although the physiological mechanism is still unclear (Yanagawa et al 1999, Chang et al 2001, Kim et al 2003, Alfonso et al 2004, Lehtonen et al 2004, Xin et al 2005. Previous studies have reported that an increased level of PRDX1 might be involved in the protection of cancer cells against various therapeutic challenges ( Butzke et al 2004, Song et al 2009). Consistent with these reports, this study demonstrated that the induction of PRDX1 by proteasome inhibition compromised any antitumoral cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRDX1 expression is also elevated in most cancers, although the physiological mechanism is still unclear (Yanagawa et al 1999, Chang et al 2001, Kim et al 2003, Alfonso et al 2004, Lehtonen et al 2004, Xin et al 2005. Previous studies have reported that an increased level of PRDX1 might be involved in the protection of cancer cells against various therapeutic challenges ( Butzke et al 2004, Song et al 2009). Consistent with these reports, this study demonstrated that the induction of PRDX1 by proteasome inhibition compromised any antitumoral cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of PRDX is inducible by various stimuli including H 2 O 2 , okadaic acid (OA), 12-O-tetradecanoylphorbol 13-acetate (TPA), and butylated hydroxyanisole, which protects cells from these stimuli , Immenschuh et al 2002, Wijayanti et al 2008). Furthermore, an increased level of PRDX1 was reported to be involved in the protection of cancer cells against various therapeutic challenges by neutralizing ROS and modulating the related signaling pathways (Butzke et al 2004, Song et al 2009). These findings indicate that PRDX1 functions as an important regulator of resistance against cancer therapy, in which induction might be an adaptive response of cells to various stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these proteins, including three from sea hares, are known to be L-amino acid oxidases (Iijima et al, 2003;Jimbo et al, 2003;Butzke et al, 2004), but the cofactors responsible for oxidase activity have not been experimentally demonstrated. These studies differ in their findings as to whether the proteins are bacteriostatic or bactericidal (Yamazaki et al, 1990;Otsuka-Fuchino et al, 1992;Melo et al, 1998;.…”
mentioning
confidence: 99%
“…These studies differ in their findings as to whether the proteins are bacteriostatic or bactericidal (Yamazaki et al, 1990;Otsuka-Fuchino et al, 1992;Melo et al, 1998;. In addition to the interesting biological roles these proteins may play for their host organisms, some may also have practical industrial or medical uses, yet none have been successfully expressed in high output systems such as bacteria (Obara et al, 1999;Torii et al, 2000;Petzelt et al, 2002;Butzke et al, 2004;Cummins et al, 2004).…”
mentioning
confidence: 99%
“…Following the work, LAOs have been identified from other species of sea hares such as Dolabella auricularia albumen gland (dolabellanin A) (Iijima et al 2003), A. punctata purple fluid (APIT) (Butzke et al 2004(Butzke et al , 2005 and A. californica ink (escapin) .…”
Section: -2 Lao In Fishmentioning
confidence: 99%